Análisis Factorial Del Cuestionario Del Perfil Vigorexico (CPV) (2014)
In order to determine the dimensions - factors that explain and validate the Profile Questionnaire vigoréxico ( CPV ) from the factor analysis , a total of 169 participants , all male gym users that were approved within a few criteria proposed inclusion. With age of M = 25.63 and SD = 7.2 , and from one type of research with quantitative methodology instrumental design , data were processed in a matrix which was analyzed in SPSS and factor analysis was calculated , the reliability and were correlated between the item and the test. The results demonstrated reliable level of Cronbach's alpha coefficient of .72 which measures the internal consistency of the test values. Correlations between test item and identified four items that were removed ; by the side of the factor analysis, the variance of the CPV is explained from 63.27 % from the Kaiser- Meyer- Olkin (KMO ) test, extracting the rotated factors yielded seven factors (Factor 1. social comparison image body , Factor 2 . cognitive rating body image dissatisfaction , Factor 3 . nutritional Supplements , Factor 4 . Frequency of exercise , Factor 5 . Anxiety train and expose the body shyness , Factor 6 . Self- perception of Body image thin , Factor 7 , concern about physical appearance ) that were grouped into three dimensions: Dimension 1 , Assessment of Body Image , Dimension 2 , thinking and behaviors related to nutritional intake , and Dimension 3 , thoughts and behaviors associated to exercise. Sociodemographic characteristics of the population are mostly aged between 18 and 31 years of age , and higher education , singles are also described. We conclude that the CPV is valid and reliable for measuring and valuing vigoréxico profile. We propose new studies in this line as adaptations and regulatory groups.